COORDINATION OF A MULTI-ECHELON SUPPLY CHAIN USING SPANNING REVENUE SHARING CONTRACT - Min, Zhao; Luong, Huynh Trung; Shafiq, Muhammad (International Journal of Industrial Engineering: Theory, Applications and Practice, 2020)
Under spanning revenue sharing contract arrangement, leading member of the supply chain negotiates for contract parameters with all other members of a multi-echelon supply chain. The downstream member simultaneously shares a specific percentage of the revenue with all other members of the supply chain. This paper investigates coordination of a three-level supply chain using spanning revenue sharing contract. The proposed contract is designed to coordinate a supply chain comprising a manufacturer, a distributor and a retailer facing stochastic demand. Wholesale price contract is used as a benchmark to evaluate the performance of the proposed contract. The conditions for coordinating the supply chain when (1) retailer is a decision maker and (2) distributor is a decision maker, are discussed under the arrangement of spanning revenue sharing contract with revenue sharing mechanism of equal additional and equal increase in percentage profit for each stakeholder. Furthermore, numerical experiments are conducted to analyze practical implementation and implications of the proposed mechanism. The research also analyzes how contract parameters affect individual profit of the retailer, the distributor, and the manufacturer under win-win solution for the participants. This research further illustrates that spanning revenue sharing contract can coordinate the supply chain with win-win solution for the participants.